Sustainable Manufacturing Processes. - Narayanan, R. Ganesh (Elsevier, 2022)
Sustainable Manufacturing Processes provides best practice advice on sustainable manufacturing methods, with examples from industry as well as important supporting theory. -- Edited summary from book.
4.4.3 Machining with surface textured tools
Keywords: Manufacturing processes -- Environmental aspects.; elektronické knihy; electronic books